Use of Silicone Tubes as Antiadhesion Devices in a Modified Two-Stage Flexor Tendon Reconstruction in Zone II: A Retrospective Study - Li, Yen-Wei; Ma, Ching-Hou; Huang, Hui-Kuang; Lin, Kai-Jen; Wu, Chin-Hsien; Tu, Yuan-Kun (The Journal of hand surgery (American ed.), 2023)
This study aimed to assess the outcome of a modified two-stage flexor tendon reconstruction using silicone tubes as antiadhesion devices while performing simultaneous tendon grafting. From April 2008 to October 2019, 16 patients (21 fingers) with zone II flexor tendon injuries, who sustained failed tendon repair or neglected tendon laceration, were treated by a modified two-stage flexor tendon reconstruction. The first stage of treatment comprised flexor tendon reconstruction with interposition of silicone tubes to minimize fibrosis and adhesion around the tendon graft; the second stage of treatment comprised silicone tube removal under local anesthesia. The patient median age was 38 (range, 22–65) years. After a median follow-up period of 14 (range, 12–84) months, the median total active motion (TAM) of fingers was 220° (range, 150–250°). Excellent and good TAM ratings were identified in 71.4%, 76.2%, and 76.2% according to the Strickland, modified Strickland, and American Society for Surgery of the Hand (ASSH) evaluation systems, respectively. At follow-up, complications included superficial infections in two fingers of one patient whose silicone tube was removed 4 weeks postoperatively. The most common complication was a flexion deformity of the proximal interphalangeal joint (four fingers) and/or distal interphalangeal joint (nine fingers). The rate of failed reconstruction was higher in patients with preoperative stiffness and infection. Silicone tubes are suitable antiadhesion devices, and the modified two-stage flexor tendon reconstruction technique is an alternative procedure with a shorter rehabilitation period for complicated flexor tendon injury, compared with current popular reconstructions. Preoperative stiffness and postoperative infection may compromise the final clinical outcome. Therapeutic IV.